Application of Electronic Land Certificates in Indonesian Digital Legal Perspective - ., Richard (Journal of Ecohumanism, 2025)
This research on the existence of electronic certificates raises profound questions about legal certainty. One of the main challenges is to ensure that electronic certificates do not have the same legal force as physical certificates, so the problem is how to implement electronic land certificates in the perspective of Indonesian digital law and the challenges of implementing electronic land certificates in the perspective of Indonesian digital law. The aim is to find out and examine the implementation of electronic land certificates in the perspective of Indonesian digital law. The results of the study are that electronic certificates are expected to be effective in national land management, in various aspects. Specifically for the aspect of internet availability for rights holders, it will be ensured that people who live in less internet-friendly locations will be able to be served at the land office using the Land Office's internet infrastructure and some of the challenges are in terms of Data Security factors, Technology Infrastructure, Education and Training, Legal Compliance, Accessibility and Dependence on Technology.